Advanced Practice Nursing Education: Challenges and Strategies - Cynthia Fitzgerald; Ira Kantrowitz-Gordon; Janet Katz; Anne Hirsch (Hindawi Limited, 2012)
Nursing education programs may face significant difficulty as they struggle to prepare sufficient numbers of advanced practice registered nurses to fulfill the vision of helping to design an improved US healthcare system as described in the Institute of Medicine's "Future of nursing" report. This paper describes specific challenges and provides strategies to improve advanced practice nursing clinical education in order to ensure that a sufficient number of APRNs are available to work in educational, practice, and research settings. Best practices are identified through a review of classic and current nursing literature. Strategies include intensive interprofessional collaborations and radical curriculum revisions such as increased use of simulation and domestic and international service work. Nurse educators must work with all stakeholders to create effective and lasting change.